Fuzzy Filters of a Po Ternary ?- Semi Groups - Kishore Kanaparthi, A. Gangadhara Rao, Koppula Jaya Babu, Gudimella V. R. K. Sagar (Mathematical Statistician and Engineering Applications, 2022)
We developed the notions of fuzzy filters, PO left (right) filter, fuzzy filters generated by a fuzzy subset and showed that C is a nonempty PO left filter iff the characteristic function is FLF and the disjoint collection of family of fuzzy filters is also fuzzy filter. We also showed if h is a FLF, then is a FPRI, any FF h is a fuzzy n-system and the FF generated by h is the collection of FFs containing h.